Scaling-Up SME Access to Financial Services in the Developing World - International Finance Corporation (Washington, DC, 2015)
Small and medium enterprises (SMEs) play a major role in economic development, particularly in emerging countries. Access to finance remains a key constraint to SME development in emerging economies. Closing the credit gap for formal SMEs will be less daunting than for informal SMEs. The SME finance gap is the result of a mismatch between the needs of the small firms and the supply of financial services, which typically are easier for larger firms to access. Deficiencies in the enabling environment and residual market failures have motivated government interventions to foster SME access to financing. The stocktaking exercise confirms the rise in various parts of the world of specific business models aimed at providing financial services to SMEs in a cost-effective manner. Effective SME financing models can be implemented in different country and market environments, but greater outreach is achieved in the most developed environments for the financial sector. Although SME banking and microfinance models are successfully being rolled out in an increasing number of countries and regions, equity financing remains a challenge in developing economies. The role of international finance institutions (IFIs) and development finance institutions (DFIs) to foster SME financing in the developing world has been significant so far. Increasing access to finance can only be successful if qualitative aspects are taken into account.